Reflections On Crossing The Boundaries Between Public And Private Law In Implementing The “European Green Deal." - Tomasz Bojar-Fijalkowski (Administrative and Environmental Law Review, 2021)
Climate change brings new challenges to the world. With its high environmental standards, the European Union is one of the most active players in global climate action. We are currently witnessing an extremely rapid process of transforming the political doctrine of the European Union into hard-law standards legal system. The so-called "European Green Deal" implements ideas of sustainable development in the area of, among others, energy, waste, but also transport, construction and electronic equipment sectors. One of the instruments for implementing the "European Green Deal" is the "Circular Economy", which, using European Union law, profoundly interferes with the economic freedoms of entrepreneurs but also consumers. Observing these activities can be interesting, especially when viewed from a certain distance and critical perspective. This text is devoted to analysing selected regulations constituting the currently created "European Green Deal" and its agenda. It also aims to indicate regulations interference in the sphere of private law, which has not yet been so much the domain of environmental law. The author presents a hypothesis on a gradual transgression of the traditional boundary between public and private law or the blurring of that boundary in the case of recent environmental legislation of the European Union.The dogmatic-legal analysis applied to the currently binding regulations for a fuller understanding also requires the application of the historical-legal method to earlier regulations. Their joint application makes it possible to indicate the direction of the new law dedicated to implementing the newest environmental-legal doctrine of the European Union. The layout of the study was subordinated to this aim, as well as its structure. The study is based on national and international literature on business law, environmental law and administrative law. Legal status up to date as of 31.07.2021.